Effect of Different Cryopreservation Regimens on Some Characteristics of Embryonic Neuronal Cells - Goltsev, A. N.; Gurina, T. M.; Babenko, N. N.; Ostankov, M. V. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of different cryopreservation regimens on the integrity of embryonic neuronal cells (ENC) according to the criteria of nuclear cell number in suspension, their viability and adhesive potential was studied. There was noted the dependency of the ENC morphofunctional characteristics both on cooling rate and the overcooling value of a sample. The possibility of a selective effect of different cryopreservation regimens on a subpopulation composition of embryonic brain cells was under consideration.